The Learning Company : A Strategy for Sustainable Development - Pedler, Mike (Mike John); Burgoyne, John and Boydell, Tom (London McGraw-Hill, 1997)
The new edition of this successful book by top authors Pedler, Burgoyne and Boydell is fully revised for today's organizations. The authors position your company at the current stage in its development, and help you create a programme for the future.
Include Illustrations and Index
Keywords: Organizational learning